Dialoguing across the centuries: on some challenges of translating medieval french works today (Colloquia Comparativa Litterarum, 2025)
Every translation is a dialogue between multiple voices. The specific features of medieval literature make its translation both stimulating and complex, requiring cultural and artistic mediation to preserve the spirit and form of the works. Translating French medieval texts involves not only conveying meaning, but also recreating a complex cultural and aesthetic experience. This process requires balancing between faithfulness to the source text, adaptation to modern sensibilities and respect for the artistic form, in order to achieve a cultural encounter that transcends centuries.
Keywords: medieval literature; translation; faithfulness; adaptation